Fiscal multipliers during consolidation: evidence from the European Union - Alessandro Cugnasca; Philipp Rother (European Central Bank (ECB), 2015)
This paper investigates the impact of fiscal consolidation on economic growth in European Union countries, between 2004 and 2013. We construct a new dataset of exogenous fiscal adjustments, relying on legally binding recommendations issued to countries under Excessive Deficit Procedure, and we identify exogenous policy changes by using this dataset as instrumental variable in a GMM framework. We estimate the size of the fiscal multiplier both in a linear setting as well as in a state-dependent setting, considering four different circumstances: the state of the business cycle, the degree of openness to trade, the composition of the fiscal adjustment and the presence of a stressed credit market, as manifested by an impaired monetary policy transmission. We find that the size of the multiplier varies significantly under the various states: the distribution of multipliers is quite asymmetric, and a few consolidation episodes yield multipliers above one. We find that the composition of the fiscal adjustments is crucial in containing the output cost of consolidation, and in determining its persistence. Fiscal adjustments made via cuts to transfers and subsidies, or via tax increases, are usually associated with multipliers at or below unity, even when the economy is in recession. We also find evidence of confidence effects when consolidation is made under stressed credit markets and high interest rates. In a small number of episodes, involving open economies benefitting from confidence effects, we find that fiscal adjustments seem to be expansionary.
Keywords: C33; E62; 330; fiscal multiplier; fiscal policy and growth; panel data